Application of laser biospeckle technique for the analysis of artificially introduced local dynamics in apple fruit. (29th August 2018) - Retheesh, R; Thomas, Dennis; Zaheer Ansari, Md; Varghese, Bejoy; Radhakrishnan, P; Mujeeb, A
Abstract: Laser biospeckle technique has been extensively used as a significant characterization tool to analyze the complex inner dynamics involved in both biological and non-biological processes. The technique has been widely applied in the field of biology, medicine and agriculture as well as in the chemical and pharmaceutical industries. Among the challenges in biology or agriculture, one of the tasks is the assessment of the local dynamics of biological specimens. We report on an optical imaging technique, the laser biospeckle to assess the local dynamics introduced on selected biological specimens subjected to mechanical and thermal loads. This study also aimed to explore the technique in detecting the early stages of biological activities. An experimental configuration of the biospeckle laser imaging technique was used to assess the monitoring and prediction of the bruising on fruit surfaces within a specified time. The methods utilized to interpret the biospeckle data allowed pre-disposition detection of the formation of internal bruising in the early stages after the occurrence of a mechanical or thermal impact.